Bronchial Hyperresponsiveness in Farmers: Severity and Work-Relatedness - Saso Stoleski; Jordan Minov; Jovanka Karadzinska-Bislimovska; Dragan Mijakoski (ID Design Press, 2014)
OBJECTIVE: To evaluate the prevalence of respiratory symptoms, lung function and bronchial hyperresponsiveness in farmers, with emphasize to their severity and work-relatedness due occupational risk factors and farming characteristics. METHODS: A cross-sectional survey was performed including 60 cow breeders aged 21 to 65 years, compared to an equal number of agricultural farmers matched by age, job exposure duration, and smoking status. We have used a questionnaire to record the chronic respiratory symptoms, detailed work history, specific farming activities and tasks performed, and smoking history. Evaluation of examined subjects also included lung function spirometry tests, and bronchial hyperresponsiveness testing. RESULTS: We found higher prevalence of work related respiratory symptoms in the last 12 months in cow breeders with significant difference for phlegm (P = 0.039), and wheezing (P = 0.026). Mean values of all spirometric parameters were lower in cow breeders, reaching significance for MEF50 (P = 0.001) and MEF75 (P = 0.000). Significant difference was found for mild bronchial hyperresponsiveness among cow breeders with job exposure of more than 15 years. The risk of developing work-related respiratory symptoms increased significantly with full-time farming, exposure to gases and vapors, and keeping more than 10 cows. CONCLUSION: Our data suggest that workplace exposure in farmers may cause respiratory impairment which is closely related to its duration, characteristics, and intensity. The results suggest that cow breeders in general have higher rates of work-related respiratory symptoms and bronchial hyperresponsiveness than agricultural farmers, whereas their severity increases with an increase in frequency and duration of animal contact.
Keywords: work-related respiratory symptoms; farming; Questionnaire; cow breeders; Spirometry; airway responsiveness